The Relationship Between Burnout and Workload Among Nurses at Hospital X Surabaya - Syaiful Adam; Nyoman Anita Damayanti (Publikasi Indonesia, 2025)
Burnout is a serious problem among healthcare professionals, such as nurses and doctors. Burnout is associated with a number of adverse consequential outcomes in health care. As many as 37.8% were in medium and high level burnout. Knowing some of the factors that cause burnout syndrome and how to manage burnout as a preventive measure against the incidence of burnout in nurses at X Surabaya hospital The method used in writing this article is descriptive analytics, by collecting secondary data obtained from the Department of Nursing. Factors such as length of employment, education and position, and workload can affect the level of burnout in nurses at Hospital X. Management strategies that can be applied to prevent burnout are stress management, organizational intervention (creating a comfortable atmosphere, rewarding and recognizing employee contributions), managing workload, and can create conditions where employees can freely manage from the workload received in the form of Job Control.